A benzothiadiazole-based covalent organic framework for highly efficient visible-light driven hydrogen evolution. Issue 83 (18th September 2020) - Wang, Guang-Bo; Li, Sha; Yan, Cai-Xin; Lin, Qian-Qian; Zhu, Fu-Cheng; Geng, Yan; Dong, Yu-Bin
Abstract : A benzothiadiazole-based covalent organic framework, which can be a high-performance platform for efficient visible-light driven hydrogen evolution, is reported. Abstract : We demonstrate herein a newly designed benzothiadiazole-based covalent organic framework through an imine linkage with high crystallinity, excellent chemical stability and significant light absorption ability, which was further applied as a high-performance platform for efficient visible-light driven hydrogen evolution.